2018
DOI: 10.1136/bmjopen-2017-019742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of differentiating exercise guidance based on a patient’s level of low back pain in primary care: a mixed-methods systematic review protocol

Abstract: IntroductionLow back pain (LBP) is one of the health conditions that lead to the most disability worldwide. Guidelines aimed at management of LBP recommend non-invasive and non-pharmacological management, including patient education, advice to stay active and exercise therapy; however, the guidelines offer no recommendation as to the allowable level of pain during exercise or how specific levels of pain should be reflected in the stage and progression of exercises or activities. The purpose of this review is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
14
0
2
Order By: Relevance
“…For acute non-specific low back pain that does not have serious pathology (red flags have been excluded), initial reassurance, advice to stay active and self-management are all that is needed [ 6 , 7 , 9 , 11 ]. Self-management can include self-exercises and education from reading booklets or being involved in on-line education for low back pain [ 16 ] (Table 1 ).…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…For acute non-specific low back pain that does not have serious pathology (red flags have been excluded), initial reassurance, advice to stay active and self-management are all that is needed [ 6 , 7 , 9 , 11 ]. Self-management can include self-exercises and education from reading booklets or being involved in on-line education for low back pain [ 16 ] (Table 1 ).…”
Section: Preventionmentioning
confidence: 99%
“…Guidelines recommend the non-pharmacological and non-invasive management [ 6 ]. These include the provision of advice to stay active and the use of patient education and exercise therapy [ 6 ]. Guidelines regularly recommend the use of physical exercise for non-specific LBP [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have shown that exercise therapy results in the reduction of LBP no general consensus exists regarding the most efficacious approach. ( Jorgensen et al, 2018 ; Nguyen et al, 2017 ). However, it has been shown that core stability exercises may result in better coping strategy for dealing with the pain.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous management strategies exist for the treatment of chronic LBP. The initial treatment options are typically noninvasive and include; pharmacological medications, manual therapy, and exercise therapy ( Jorgensen et al, 2018 ). Exercise therapy is one of the most common treatment approaches for the management of LBP ( Aboagye et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…30 PT aims to improve posture and mobility, reduce pain and promote relaxation and muscle stabilization, by providing exercise therapy and patient education. 31 The Akbari and colleagues' model 32 include pain catastrophizing beliefs, family functioning, kinesiophobia and depression as mediators between the exogenous variables (eg pain intensity) and endogenous variables (eg functional disability). The present study included the same exogenous and endogenous variables and analyzed how subjective suffering was related to illness perceptions, pain intensity and psychological morbidity and their direct and indirect effects on functional disability in chronic LBP, in patients undergoing PT.…”
mentioning
confidence: 99%